Influence of Carbon Fiber Addition in Physical-Thermal Properties of Composites Obtained by RTM - Montoro, Sergio Roberto; Paula, Isabelle Catarina de; Brocks, Thatiane; Bandeira, Cirlene Fourquet; Voorwald, Herman Jacobus Cornelis; Cioffi, Maria Odila Hilário (Journal of Research Updates in Polymer Science, 2013)
This work aims to study the influence of carbon fibers addition in physical-chemical properties of bicomponent epoxy resin, produced by POLIPOX, in a composite obtained by RTM. Thermal analyses (DSC (Differential Scannig Calorimetry), TGA (Thermal Gravimetric Analysis) and DMA (Dynamic-mechanical Analysis) were performed in order to compare the results and observe the reinforcement influence on the resin properties. Increased glass transition values and degradation temperatures show that fibers cause a reduction in the molecular motion of polymer chains.